THE INFLUENCE OF VIDEO LEARNING ON UNDERSTANDING ENGLISH LEARNING DURING PANDEMIC - Marhadi; Chairunnisa (Dialectical Literature and Educational Journal, 2023)
The first aim of this research is to explore the influence of video learning on understanding English learning during the pandemic at Mentari Ilmu Islamic Junior High School Karawang. Second, it aims to explore the effectiveness of video learning. Third, it aims to explore the supporting and inhibiting factors of video learning. This research was descriptive analysis research. The data collection techniques of this research used triangulation consisting of observation, interviews, and documentation. The participants consisted of three English teachers and sixty-one students in three classes. The data were analyzed using data reduction, display, and verification. The first finding is the influence of video learning on the understanding of 7th-grade English learning during a pandemic, there were 75,4% of students agreed that using video learning media in the online learning process during the pandemic had a good influence on their understanding. The second finding is the effectiveness of video learning on the understanding of 7th-grade English learning during a pandemic, there were 68,9% of students agreed that using video learning in the online learning process during the pandemic had a good effect on their understanding. The last finding of this research shows that learning videos for teachers have supporting factors and inhibiting factors in their use; for example: more easily understood by students because it contains audio-visual elements, do not make students bored quickly, and are easier to develop, while the inhibiting factor from using videos learning is that it takes more time in the preparation.